2017
DOI: 10.1016/j.jpainsymman.2017.06.012
|View full text |Cite
|
Sign up to set email alerts
|

A Patient-Centered Approach to Research on Palliative Care for Patients With Advanced Illnesses and Their Caregivers

Abstract: Background People with advanced, serious illnesses experience a high burden of physical and psychosocial symptoms, limitations in functioning, and declining quality of life (QOL) over the course of their illness. Caring for these patients can take a significant physical and emotional toll on their caregivers as well. Palliative care has been defined as ''patient-and family-centered care that optimizes QOL by anticipating, preventing, and treating suffering. Palliative care throughout the continuum of illness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Patient engagement, a guiding principal which drives the PCORI research agenda, establishes a partnership among practitioners, patients, and their families to ensure that decisions respect patients’ wants, needs, and preferences, and that patients have the education and support they need to make decisions and participate in their own care [ 39 ]. PCORI works to engage patients and stakeholders in every phase of research, with a goal of better understanding treatment effects, which may differ across patient populations [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient engagement, a guiding principal which drives the PCORI research agenda, establishes a partnership among practitioners, patients, and their families to ensure that decisions respect patients’ wants, needs, and preferences, and that patients have the education and support they need to make decisions and participate in their own care [ 39 ]. PCORI works to engage patients and stakeholders in every phase of research, with a goal of better understanding treatment effects, which may differ across patient populations [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCORI funds comparative clinical effectiveness research (CER) that addresses important health and healthcare-related dilemmas faced by patients, caregivers, clinicians, and health systems. By comparing two or more interventions for which evidence of efficacy already exists, and by engaging key patients and stakeholders throughout the research process, PCORI-funded trials have the potential to accelerate the dissemination and implementation of research findings in real-world settings [ 18 ]. PCORI, through its Addressing Disparities research portfolio, has made significant investments in trials that conduct CER to address health and healthcare disparities.…”
Section: Introductionmentioning
confidence: 99%
“…Federal funding through the National Institutes of Health (NIH) and its centers has provided both research and training grants in palliative care . The Patient‐Centered Outcomes Research Institute also has funded comparative effectiveness studies in palliative care . Palliative care scientists have established research consortia to facilitate multisite palliative care trials and to develop the research capacity of investigators to build the evidence base for palliative care .…”
Section: Strategy 1: Stimulating the Science In Specific Gap Areasmentioning
confidence: 99%
“…73,74 The Patient-Centered Outcomes Research Institute also has funded comparative effectiveness studies in palliative care. 75 Palliative care scientists have established research consortia to facilitate multisite palliative care trials and to develop the research capacity of investigators to build the evidence base for palliative care. 76,77 These consortia, along with palliative care funding opportunities from the American Cancer Society (ACS) and the American Academy of Hospice and Palliative Medicine, have included an investment in investigator training and professional development, ensuring the future development of the field.…”
Section: Funding and Investigator Trainingmentioning
confidence: 99%
“…1,7 In response to these recommendations and unmet research needs, PCORI identified CER on palliative care as a priority area for funding. 15 In March 2016, PCORI convened a large multistakeholder palliative care workgroup meeting attended by 82 stakeholders that included patients, patient and caregiver advocates, clinicians, palliative care researchers, representatives of public and private payers, federal and private research funding organizations, clinical specialty societies, and industry representatives. The public was also invited to listen to the discussion at the workshop.…”
Section: Introductionmentioning
confidence: 99%